The butterfly as companion : meditations on the first three chapters of the Chuang Tzu - Wu, Kuang-ming (SUNY series in religion and philosophy, 1990)
"Chuang Tzu's first three chapters are arranged into free verse (in Chinese, in the original word order) and translated, nearly word-for-word, with extensive critical glosses vis-a-vis over fifty Chinese, Japanese, and Western commentators. The exegetical, philosophical, and contemporary implications of these chapters are then meditated upon. Here, in Chuang Tzu's world, all strivings are a play, parodying stories and arguments; each plays off of and refers to the others. Chuang Tzu lived during the third and fourth centuries B.C. Historically, he is the foremost spokesman for Taoism and its legendary founder, Lao Tzu. It was mainly due to the influence of Chuang Tzu that Indian Buddhism was transformed in China into Ch'an into the unique vehicle we usually call by its Japanese name, Zen. This is the most thorough presentation to date of the Chuang Tzu's poetic beauty, philosophical insights, and unity"--Contratapa.